The Bay Leaves Active Compounds and Its Lipid Oxidative Inhibition Activity in Bulk Cooking Oil - Wahyudi, Vritta Amroini; Aini, Afifah Nuril; Puspita, Dian; Dewi, Ayu Ramadhani Kumala (Universitas Muhammadiyah Yogyakarta, 2021)
Cooking oil is one of the basic human needs. Improving the quality of bulk cooking oil is necessary because it is related to economic reason. The bulk cooking oil have a lower price than brand package oil, of course. Based on these reasons, research is needed on the use of antioxidants to improve the quality of bulk cooking oil. This study aims to identify the phytochemicals of bay leaves extract through TOF profiling, analysis of iodine number and acid number of bay leaves extract against bulk cooking oil. TOF profiling was carried out to see whether bay leaves had chemical compounds that supported antioxidant activity which had an impact on the inhibition of fat oxidation. The research consisted of 4 stages: 1) extraction and fractionation of bay leaves, 2) TOF profiling of bay leaves extract, 3) application of bay leaves extract to bulk cooking oil, 4) analysis of iodine and acid numbers. Profiling TOF of the bay leaves extract showed 3 peaks : C6H13NO5 (cyclohexanol, galactose, and fructose derivatives), C11H14O5 (pyran and furan), andC11H19NO3 (morpholine derivate). According to SNI, the acid value maximum 0.6 mg KOH/g. Iodine value minimum is 45 g I2/ 100 mL (SNI 3741 : 2013). Based of this data standart, this study recommended use bay leaves extract in concentration 0.80%. The addition of bay leaves extract as much as 0.80% showed an iodine number of 48.2 g I2/100 mL and an acid number of 0.34 mg KOH/g where the positive control TBHQ showed an iodine number of 48.7 g I2/100 mL and an acid number of 0.19 mg KOH/g.